The cultivation - cattle complex in western Darfur - Wilson, R.T.; Bailey, L.; Hales, J.; Moles, D.; Watkins, A.E. (Elsevier, 1980)
Discusses the cultivation/cattle complex in Western Darfur, Sudan by giving greater emphasis on traditional rainfed agriculture, small-scale irrigation and animal husbandry. Presents data on agronomy and yield of traditional rainfed crops, on climatology, on livestock population and on livestock production parameters.